INDONESIAN HIGH SCHOOL STUDENTS’ METACOGNITIVE AWARENESS BY GENDER AND GRADE: VALIDATING MAI USING IRT ANALYSIS - RUSMANA, AI NURLAELASARI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
Metacognition is significant in fostering students' academic success and self-regulated learning. This study explores the metacognitive awareness of Indonesian high school students in science learning, with a focus on the effects of gender and grade level. Using the Metacognitive Awareness Inventory (MAI), a widely utilized self-report instrument, data were collected from 185 Indonesian high school students, majoring in science, across 10th and 11th grades in public and private schools. To ensure the validity and reliability of the instrument within this context, the study employed an Item Response Theory (IRT) framework using the TAM package in R. The analysis examined dimensionality, item fit, and reliability metrics, ensuring the suitability of the 19-item MAI subset. Subsequent analyses using two-way ANOVA in IBM SPSS Statistics 29 evaluated differences in metacognitive awareness across gender and grade levels. IRT analysis confirmed the suitability of the MAI for measuring high school students’ metacognitive awareness, identifying two dimensions: knowledge of cognition and regulation of cognition. All items showed good fit to the IRT framework, and item as well as person reliability across dimensions was fair to good categories. With regards to high school students’ metacognitive awareness, female students generally demonstrated higher awareness than male students, particularly in regulation of cognition dimension. The findings align with prior research emphasizing the influence of biological and social factors on establishing gender differences in metacognition. Additionally, 10th-grade students demonstrated greater metacognitive awareness in the knowledge of cognition dimension than 11th graders, suggesting that younger students may engage more in reflective practices and maintain a stronger innate curiosity, which fosters metacognitive development. ABSTRAKMetakognisi memiliki peranan penting dalam mendorong keberhasilan akademik dan regulasi diri siswa. Penelitian ini mengeksplorasi kesadaran metakognisi siswa SMA di Indonesia dalam pembelajaran sains, dengan fokus pada variabel gender dan tingkat kelas. Dengan menggunakan Metacognitive Awareness Inventory (MAI), salah satu instrumen metakognisi yang paling banyak digunakan, data pada penelitian ini dikumpulkan dari 185 siswa SMA Indonesia jurusan sains di kelas 10 dan 11 dari sekolah negeri dan swasta. Penelitian ini menggunakan kerangka Item Response Theory (IRT) atau teori respon butir untuk menguji validitas dan reliabilitas instrumen ini pada R dengan paket TAM. Analisis validitas mencakup uji dimensi instrumen, kecocokan item, dan uji reliabilitas terhadap 19 butir MAI. Adapun analisis lanjutan menggunakan two-way ANOVA pada IBM SPSS Statistics versi 29 untuk mengevaluasi perbedaan kesadaran metakognisi berdasarkan gender dan tingkat kelas. Hasil analisis IRT mengonfirmasi kesesuaian instrumen MAI untuk mengukur kesadaran metakognisi siswa SMA, dengan mengidentifikasi dua dimensi: pengetahuan tentang kognisi (knowledge of cognition) dan regulasi kognisi (regulation of cognition). Semua item MAI menunjukkan kecocokan dengan kerangka IRT serta indeks reliabilitas item dan person pada setiap dimensi berada dalam kategori cukup hingga baik. Terkait kesadaran metakognisi siswa SMA, siswa Perempuan umumnya menunjukkan kesadaran metakognisi lebih tinggi dibandingkan siswa laki-laki, terutama pada dimensi regulasi kognisi. Temuan ini sejalan dengan penelitian sebelumnya yang menyoroti pengaruh faktor biologis dan sosial dalam membentuk perbedaan gender dalam metakognisi. Selain itu, siswa kelas 10 menunjukkan kesadaran metakognisi yang lebih tinggi pada dimensi pengetahuan tentang kognisi dibandingkan siswa kelas 11. Hal ini juga menunjukkan bahwa siswa yang lebih muda cenderung lebih sering terlibat dalam aktivitas reflektif dan mempertahankan rasa ingin tahu yang kuat sehingga mendorong perkembangan metakognisinya.